Phosphodiesterase‐5 inhibition potentiates cerebrovascular reactivity in chronic traumatic brain injury. Issue 4 (7th March 2018) - Kenney, Kimbra; Amyot, Franck; Moore, Carol; Haber, Margalit; Turtzo, L. Christine; Shenouda, Christian; Silverman, Erika; Gong, Yunhua; Qu, Bao‐ Xi; Harburg, Leah; Wassermann, Eric M.; Lu, Hanzhang; et al.
Abstract: Background: Traumatic cerebrovascular injury (TCVI), a common consequence of traumatic brain injury (TBI), presents an attractive therapeutic target. Because phosphodiesterase‐5 (PDE5) inhibitors potentiate the action of nitric oxide (NO) produced by endothelial cells, they are candidate therapies for TCVI. This study aims to: (1) measure cerebral blood flow (CBF), cerebrovascular reactivity (CVR), and change in CVR after a single dose of sildenafil (ΔCVR) in chronic TBI compared to uninjured controls; (2) examine the safety and tolerability of 8‐week sildenafil administration in chronic symptomatic moderate/severe TBI patients; and as an exploratory aim, (3) assess the effect of an 8‐week course of sildenafil on chronic TBI symptoms. Methods: Forty‐six subjects (31 chronic TBI, 15 matched healthy volunteers) were enrolled. Baseline CBF and CVR before and after administration of sildenafil were measured. Symptomatic TBI subjects then completed an 8‐week double‐blind, placebo‐controlled, crossover trial of sildenafil. A neuropsychological battery and neurobehavioral symptom questionnaires were administered at each study visit. Results: After a single dose of sildenafil, TBI subjects showed a significant increase in global CVR compared to healthy controls ( P < 0.001, d = 0.9). Post‐sildenafil CVR maps showed near‐normalization of CVR in many regions where baseline CVR was low, predominantly within areas without structural abnormalities. Sildenafil was well tolerated. Clinical Global Impression (CGI) scale showed a trend toward clinical improvement while on sildenafil treatment. Findings: Single‐dose sildenafil improves regional CVR deficits in chronic TBI patients. CVR and ΔCVR are potential predictive and pharmacodynamic biomarkers of PDE5 inhibitor therapy for TCVI. Sildenafil is a potential therapy for TCVI.